PENGARUH CITRA WARUNG STEAK TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN SEBAGAI VARIABEL MEDIASI - Untung Sriwidodo, Ernawati & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2011)
ABSTRACT The purpose of this research were to analyze the influence of image steak shop on consumer loyalty, the influence of image steak shop on consumer satisfaction, influence of customer satisfaction on consumer loyalty, and influence indirect consumers shop steak for image loyality through consumer satisfaction as a mediating variable.The populations in this study are all consumers’ steak shops in the Surakarta area. ​​ Number of samples in this study was 100 consumers in five famous steak shops in Surakarta. The sampling method using accidental sampling. To test this hypothesis, researchers used path analysis, while for processing the data using SPSS. To build consumer loyalty that consumers do not move to another place and would recommend it to others, then the steak entrepreneurs must constantly improve the image of the Corporate and consumer satisfaction. Keywords: image of the steak shop, consumer satisfaction, consumer loyalty